PRODUCT INNOVATION, MARKETING INNOVATION AND BUSINESS PERFORMANCE RELATIONSHIP OF MALAYSIAN PRODUCT INDUSTRIES: MEDIATING EFFECT OF DESIGN MANAGEMENT - Al-Shorman, Mohammad; Alzoughool, Sameer A A; Al qatawneh, Diaa Khalaf Ahmed; Alqudah, Tamer Hussein Ahmad; Saad, Sabrina (International Journal of Psychosocial Rehabilitation, 2020)
Due to the growing significance of design management and innovation to business performance, in particular, it is vital for the product industries to keep pace with the rapid changes of the economic model and technology that the world is heading towards. Therefore, the developed countries consider design management as a competence that comes under the umbrella of innovation management. The objectives of this study are to determine the relationship among product innovation and marketing innovation on business performance of product industries in Malaysia, to analyse the effect of product innovation and marketing innovation on design management of product industries in Malaysia, to examine the effect of design management on the business performance of product industries in Malaysia and to test the mediating effect of design management between innovation types and business performance relationship of product industries in Malaysia. The quantitative research design approach was used in this study to collect data from 386 respondents selected from the product industries in Malaysia. The required data were obtained using simple random sampling by a validated questionnaire. Furthermore, the data collected from the survey were analyzed using Partial Least Square Structural Equation Model (SmartPLS3-SEM). The results of this study showed all the direct relationships are not significant whereas, all mediating effects are significant. This study provides empirical evidence that the effect of design management on the relationship between innovation types and business performance could lead to higherbusiness performance of product industries in Malaysia. The product industries may be benefited from this study in improving their businesses as this study has come up with the critical dimensions that could lead to better business performance.